2017
DOI: 10.1039/c7sc03675b
|View full text |Cite
|
Sign up to set email alerts
|

Bulk assembly of organic metal halide nanotubes

Abstract: A single crystalline organic metal halide hybrid containing arrays of one-dimensional metal halide nanotubes is discovered for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 40 publications
6
80
0
Order By: Relevance
“…Is it possible to use metal halide octahedra as building blocks to build 1D tubular structure? By using protonated hexamethylenetetramine (HMTA, C 6 H 13 N 4 + ) as cationic moieties, a bulk assembly of 1D metal halide nanotubes with a chemical formula of (C 6 H 13 N 4 ) 3 Pb 2 Br 7 was recently developed by our group (Figure 7(g)) [21]. This new material can display the intrinsic properties of individual nanotubes due to the complete isolation and strong quantum confinement by a bulky wide-bandgap organic moiety.…”
Section: D Metal Halide Hybridsmentioning
confidence: 99%
“…Is it possible to use metal halide octahedra as building blocks to build 1D tubular structure? By using protonated hexamethylenetetramine (HMTA, C 6 H 13 N 4 + ) as cationic moieties, a bulk assembly of 1D metal halide nanotubes with a chemical formula of (C 6 H 13 N 4 ) 3 Pb 2 Br 7 was recently developed by our group (Figure 7(g)) [21]. This new material can display the intrinsic properties of individual nanotubes due to the complete isolation and strong quantum confinement by a bulky wide-bandgap organic moiety.…”
Section: D Metal Halide Hybridsmentioning
confidence: 99%
“…Recently,b roadband white-light emission as an intrinsic property has been realized in h110i-oriented corrugated 2D or 1D organolead halide perovskites,w hich is attributed to the formation of self-trapped excitons. [6][7][8][9][10][11][12] This promising class of white-light emitters is amenable to crystal engineering for further enhancing their photoluminescence properties. [13][14][15][16][17][18] However,the intrinsic moisture instability of lead perovskites has not been fully addressed.…”
mentioning
confidence: 99%
“…Biwu Ma et al reported the synthesis and characterization of a monocrystalline bulk assembly of organic metal halide nanotubes composed of (C 6 H 13 N 4 ) 3 Pb 2 Br 7 ((HMTA) 3 Pb 2 Br 7 ), the structure of which is shown in Figure a. This unique 1D tubular structure combines strong quantum confinement with highly localized electronic states, thus leading to the formation of self‐trapped excitons that generate a wideband and strongly Stokes‐shifted yellowish‐white emission with a PL quantum efficiency (PLQE) of ≈7% . In the same year, You et al demonstrated a single‐phase HOP ferroelectric material, Me 3 NCH 2 ClMnCl 3 (TMCM‐MnCl 3 ), during the formation of red block single crystals.…”
Section: Various Approaches To Construct Hop Spin‐related Optoelectromentioning
confidence: 99%
“…The inset in the bottom right corner is the corresponding FFT image. a) Reproduced with permission . Copyright 2017, The Royal Society of Chemistry.…”
Section: Various Approaches To Construct Hop Spin‐related Optoelectromentioning
confidence: 99%